Orientasi Religiusitas dan Efikasi Diri dalam Hubungannya dengan Kebermaknaan Pendidikan Agama Islam pada Mahasiswa IAIN Palopo - Tahaha, Hisban; Rustan, Edhy (Jurnal Studi Agama dan Masyarakat, 2017)
This research aims to find out the influence of religious orientation and self efficacy on the meaning of Islamic education. Technique of data analysis of this research use correlation and regression statistic test conducted by IAIN Palopo student with 75 respondents. The design of this research is the correlation design between the relation of religiosity orientation with the meaning of Islamic religious education, the relationship of self efficacy with the meaning of Islamic religious education, and the relation of religious orientation and self efficacy to the meaningfulness of Islamic religious education. After the research done by spreading the questionnaire, it was found that the orientation of religious self efficacy had an effect on the meaning of Islamic education either simultaneously or partially. Reflective contribution for religious orientation was 41,51%, and self efficacy was 58,49%, while for the effective contribution of religious orientation variable was 2.99%, and self efficacy variable was 4,21%. 4,6% variation meaningfulness Islamic education can be explained by the orientation of religiosity and self efficacy, while the remaining 95,4% is explained by other factors.